2021
DOI: 10.1016/j.radcr.2020.10.032
|View full text |Cite|
|
Sign up to set email alerts
|

Artery of Percheron infarction a rare anatomical variant and a diagnostic challenge: Case report

Abstract: The Artery of Percheron (AOP) is an uncommon anatomic variant that provides arterial supply to the paramedian region of the thalami and bilaterally to the rostral part of the midbrain; it is a solitary arterial trunk that branches from a proximal segment of the posterior cerebral artery (PCA). Although AOP infarction results in a characteristic pattern of ischemia, namely bilateral paramedian thalamic infarct with or without midbrain involvement, it may cause diagnostic difficulties due to the variety of its c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 25 publications
(62 reference statements)
0
17
0
Order By: Relevance
“…2 , Fig. 3 ] further contributing to delays in the diagnosis of AOP infarction [15] . Delays in performing an MRI result in a late diagnosis, significantly impacting the management and prognosis of these patients, as was the case of our patient.…”
Section: Discussionmentioning
confidence: 99%
“…2 , Fig. 3 ] further contributing to delays in the diagnosis of AOP infarction [15] . Delays in performing an MRI result in a late diagnosis, significantly impacting the management and prognosis of these patients, as was the case of our patient.…”
Section: Discussionmentioning
confidence: 99%
“…There have been reported cases of bilateral thalamic strokes, who presented mainly with sudden onset of hypersomnia and fluctuating arousal as the thalamus plays an important role in sleep regulation and in maintaining arousal. Hypersomnolence can be due to the interruption of noradrenergic and dopaminergic pathways from the ascending reticular activating system to the thalamus [ 14 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Acute AOP ischemia has great variability with respect to symmetry, size, and territory, which is mainly due to the thalamic arteries vary between individuals. These differences are related to the parent vessel from which each branch arises, the number and position of the arteries and their tributaries [ 9 , 12 , 18 ]. Paramedian bithalami of the 23 patients showed high signal intensity on FLAIR with restricted diffusion and hypointense in the ADC map (positive in 100%).…”
Section: Discussionmentioning
confidence: 99%
“…The diameter of AOP is so small that magnetic resonance angiography (MRA) cannot show it, and even digital subtraction angiography (DSA) cannot show its existence, stenosis or occlusion in most cases. Only a few authors found AOP obstruction through DSA [ 9 , 10 ]. MRI, especially diffusion weighted imaging (DWI), plays an important role in the diagnosis of acute AOP infarction.…”
Section: Introductionmentioning
confidence: 99%